O1C.1 Key features of the new preamble to IARC monographs. (April 2019) - Straif, Kurt; Guyton, KZ; Schubauer-Berigan, MK; Hall, AL; Grosse, Yann; Wild, CP
Abstract : Background: The Preamble to the IARC Monographs describes the objective and scope of the programme, general principles and procedures, and scientific review and evaluations. Since 1971, the Preamble has been updated periodically. In 2018 IARC convened an Advisory Group (AG) to Recommend an Update to the Preamble. Methods: In advance of the meeting IARC engaged with Governing Council members, WHO and senior IARC staff. In order to take into account scientific input from all stakeholders in a comprehensive and transparent way, IARC solicited online submission of scientific comments and presentations at a scientific webinar. Starting in September, the Advisory Group began to discuss the public comments and draft updates to the Preamble, working in subgroups. The AG then participated in a 3 day meeting held on 12–14 November 2018 in Lyon, France. Results: The updated Preamble confirms additional commitments to principles of scientific rigour, impartial evaluation, transparency, and consistency. Advancements in methods of systematic review provide a basis for enhancing transparency through more specific guidance to Working Group members. Specifically, reviews of exposure assessment quality will be integrated with human cancer studies and mechanistic data. The critical role of informed judgement by experts is an integral component of the Monograph evaluation process and reliance on standardized checklists would be counterproductive; the informativeness of each study will be explicitly considered in future Monographs. The key characteristics of carcinogens provide a framework for organizing mechanistic evidence and assessing its strength. The overall evaluation draws on the mechanistic, animal bioassay, and human evidence in a more integrated fashion. The AG recommended clarification regarding the distinction between Group 2A and Group 2B. Conclusions: This new Preamble will enable IARC to take advantage of the scientific and procedural advances and strengthens the transparent method for the identification of carcinogenic hazards, the first step in cancer prevention.